(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Forensic examination of physical evidence is important in the investigation of crimes. It plays a particularly important role in solving serious crimes against a person, such as murder, rape, etc. It helps the investigation to recreate the situation in which the crime was committed, to significantly judge the circle of suspects, and in some cases to irrefutably expose the culprit or, on the contrary, exclude the suspected person.